Keefektifan Model Pembelajaran JIGSAW Berbantu Flashcard dengan Pendekatan Realistik untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa di SDN 1 Wanglu - Alipah, Siti; Putra, Lisa Virdinarti (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
Learning models and strategies are important in education in Indonesia. The purpose of this study was to determine the effectiveness of applying the JIGSAW learning model assisted by flashcards with a realistic approach to improve problem solving skills at SDN 1 Wanglu. The research method used is a research approach using a quantitative approach. The type of research used is purposive sampling using non-probability sampling techniques. The results showed that the experimental class by applying the JIGSAW learning model assisted by flashcards with a realistic approach was better than the control class, it was proven that most of the students were no longer familiar with problem-solving questions in science learning, students' problem-solving abilities were maximized, this was expressed by learning Science which was originally rote and now has been overcome by applying the JIGSAW learning model assisted by flashcards with a realistic approach, so that students really pay attention to the learning process. the JIGSAW learning model has proven that aspects of problem-solving ability in science learning are included in the learning implementation plan (RPP), the textbooks used already show a balanced proportion of problem-solving stages categories. So it can be concluded that there is an effectiveness of the flashcard assisted JIGSAW learning model with a realistic approach to improve students' problem solving abilities.